1990
DOI: 10.1002/bit.260350204
|View full text |Cite
|
Sign up to set email alerts
|

Lipolytic activities of a lipase immobilized on six selected supporting materials

Abstract: Six different types of materials including PVC, chitosan, chitin, agarose, Sepharose, and Trisacryl were evaluated for their lipase-coupling efficiencies. Among those tested, chitosan yielded the highest amount of lipase (79 mg/mL packed gel) immobilized but with lowest oil hydrolytic activity (0.03 mg eq/mL gel). The amount of lipase immobilized was affected by the length of the hydrocarbon chain attached to the PVC matrix but not by the pore size of the supports used. On the other hand, the specific activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
51
1
2

Year Published

1999
1999
2010
2010

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(59 citation statements)
references
References 13 publications
5
51
1
2
Order By: Relevance
“…Many methods have been used to immobilize lipases, including adsorption or precipitation onto hydrophobic materials (Wisdom et al, 1984), covalent attachment to functional groups (Shaw et al, 1990), entrapment in polymer gels (Telefoncu et al, 1990), adsorption in macroporous anion exchange resins (Rizzi et al, 1992), microencapsulation in lipid vesicles (Balcão et al, 1996), and sol-gel entrapment Krishnakant and Madamwar, 2001). G. candidum lipases A and B were immobilized on Accurel EP 100 porous polypropylene supports, precoated with ovalbumin to increase stability in organic solvents and at elevated temperatures (Charton and Macrae, 1992).…”
Section: Immobilization Of Lipasesmentioning
confidence: 99%
“…Many methods have been used to immobilize lipases, including adsorption or precipitation onto hydrophobic materials (Wisdom et al, 1984), covalent attachment to functional groups (Shaw et al, 1990), entrapment in polymer gels (Telefoncu et al, 1990), adsorption in macroporous anion exchange resins (Rizzi et al, 1992), microencapsulation in lipid vesicles (Balcão et al, 1996), and sol-gel entrapment Krishnakant and Madamwar, 2001). G. candidum lipases A and B were immobilized on Accurel EP 100 porous polypropylene supports, precoated with ovalbumin to increase stability in organic solvents and at elevated temperatures (Charton and Macrae, 1992).…”
Section: Immobilization Of Lipasesmentioning
confidence: 99%
“…Shaw et al (9) found that the amount of lipase immobilized onto varying supports was dependent upon the length of the linker's carbon chain. The amount of protein immobilized using a linker of two carbons was considerably lower than with a linker of six to twelve carbons (9).…”
Section: Immobilization Of Lipase Frommentioning
confidence: 99%
“…Shaw et al (9) found that the amount of lipase immobilized onto varying supports was dependent upon the length of the linker's carbon chain. The amount of protein immobilized using a linker of two carbons was considerably lower than with a linker of six to twelve carbons (9). When comparing the two linkers used here (glutaraldehyde and azide), the following analogy can be made: glutaraldehyde is comparable to an arm, whilst azide is comparable to a finger.…”
Section: Immobilization Of Lipase Frommentioning
confidence: 99%
See 1 more Smart Citation
“…[119] Karbonilna grupa aktiviranog nosača reaguje sa amino grupom molekula enzima pri čemu nastaje Shiff-ova (Šifova) baza: Na ovaj način najčešće se aktiviraju neorganski nosači (staklo, keramika, alumosilikati, oksidi metala i dr.). [120][121][122][123][124] Ukoliko nosač ne sadrži amino grupu, potrebno ju je uvesti. 37 Uvođenje amino grupe vrši se u reakciji nosača i alkildiamina.…”
Section: Kovalentna Imobilizacija Enzimaunclassified